Electron migration in DNA matrix: an electron transfer reaction - Poy, Cecília Dominical; Cornélio, Marinônio Lopes (Eclética Química, 1998)
This paper brings an active and provocative area of current research. It describes the investigation of electron transfer (ET) chemistry in general and ET reactions results in DNA in particular. Two DNA intercalating molecules were used: Ethidium Bromide as the donor (D) and Methyl-Viologen as the acceptor (A), the former intercalated between DNA bases and the latter in its surface. Using the Perrin model and fluorescence quenching measurements the distance of electron migration, herein considered to be the linear spacing between donor and acceptor molecule along the DNA molecule, was obtained. A value of 22.6 (± 1.1) angstroms for the distance and a number of 6.6 base pairs between donor and acceptor were found. In current literature the values found were 26 angstroms and almost 8 base pairs. DNA electron transfer is considered to be mediated by through-space interactions between the p-electron-containing base pairs.